Comparison of 2-Year Angiographic Outcomes of Stent- and Nonstent-Assisted Coil Embolization in Unruptured Aneurysms with an Unfavorable Configuration for Coiling - Hwang, G.; Park, H.; Bang, J.S.; Jin, S.-C.; Kim, B.C.; Oh, C.W.; Kang, H.S.; Han, M.H.; Kwon, O.-K. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Stents are known to have hemodynamic and biologic effects in addition to their mechanical scaffold effect. To determine whether stents affect long-term outcomes after coiling of unruptured aneurysms, we compared angiographic outcomes at 2 years postembolization for stent- and nonstent-assisted coiled unruptured aneurysms. MATERIALS AND METHODS: Stent-assisted coiling was used in unruptured aneurysms unfavorable for simple coiling (neck size >4 mm and dome-to-neck ratio <1.5) in our practice. Therefore, 126 coiled unruptured aneurysms in total (40 [31.7%] stent group and 86 [68.3%] nonstent group) with these conditions were selected for this study. The nonstent group aneurysms were treated with multiple microcatheter technique (53 cases) or balloon-assisted technique (33 cases). Self-expandable stents were used for coiling in stent group aneurysms. No significant difference in aneurysmal characteristics (aneurysm type [sidewall/bifurcation], diameter, neck size, and dome-to-neck ratio) or angiographic outcome at embolization (packing attenuation, obliteration grade, and contrast filling) were observed between the 2 study groups. RESULTS: At 2-year follow-up visits, rates of progressive occlusion (stent group, 17/40 [42.5%] versus nonstent group, 34/86 [39.5%]) and recanalization (7/40 [17.5%] versus 18/86 [21.0%]) did not show a statistically significant difference between the 2 groups (P = .895). CONCLUSIONS: The present study did not show that additional hemodynamic and biologic effects of stents designed for neck remodeling were enough to enhance progressive occlusion and prevent the recanalization of unruptured aneurysms. Our finding suggests that stent placement provides no better long-term angiographic outcomes for unruptured aneurysms with an unfavorable configuration for coiling. DSAdigital subtraction angiographyIUinternational unitMRAMR angiography